Characterization of water quality in Bungboraped Wetland, Thailand using self organizing map for water quality management - Napon Anuttarunggoon (2020)
© 2020, Thai Society of Higher Eduation Institutes on Environment. All rights reserved. Bungboraped is the largest wetland in Thailand. The water quantity and quality, based on people’s activities around the wetland, is currently speeding up environmental degradation. The government has organized projects that aim to improve the water quality. These projects are currently having a negative affect on the quality of the water. The aim of this research was to analyze characteristics of water quality. Water parameters with 13 variables data were collected from 2004 to 2016, from 5 surface water stations located in the wetland area. Data analysis was subsequently performed using Self Organizing Maps (SOM) and Principal Component Analysis (PCA). Six distinct clusters were obtained based on the similarity of their water quality parameters. There were five clusters, where the water quality was not very good. This was related to the location and pattern of dredging and pumping of the sediment, water quantity and runoff. However, the last cluster was shown to be in good condition, because there was enough water present to self-purify, and was clearly separated for PCA. The result from this study will be the basic information leading to the activities that increase the water quality in the Bungboraped wetland.